Familial History of Autoimmune Disorders Among Patients With Pediatric Multiple Sclerosis. Issue 5 (September 2021) - Greenberg, Benjamin M.; Casper, Theron Charles; Mar, Soe S.; Ness, Jayne M.; Plumb, Patricia; Liang, Shannon; Goyal, Manu; Weinstock-Guttman, Bianca; Rodriguez, Moses; Aaen, Gregory S.; Belman, Anita; Barcellos, Lisa F.; et al.
Abstract : Background and Objective: The objective of this study was to determine whether family members of patients with pediatric multiple sclerosis (MS) have an increased prevalence of autoimmune conditions compared with controls. Methods: Data collected during a pediatric MS case-control study of risk factors included information about various autoimmune diseases in family members. The frequency of these disorders was compared between cases and controls. Results: There was an increased rate of autoimmune diseases among family members of pediatric MS cases compared with controls with first-degree history of MS excluded (OR = 2.27, 95% CI 1.71–3.01, p < 0.001). There was an increased rate of MS among second-degree relatives of pediatric MS cases compared with controls (OR = 3.47, 95% CI 1.36–8.86, p = 0.009). The OR for MS was 2.64 when restricted to maternal relatives and 6.37 when restricted to paternal relatives. Discussion: The increased rates of autoimmune disorders, including thyroid disorders and MS among families of patients with pediatric MS, suggest shared genetic factors among families with children diagnosed with pediatric MS.